2011
DOI: 10.1097/id.0b013e31822f7b97
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Loading of Freestanding Implants Using Cortical Satellite Implants: 3-Year Results of an Ongoing Prospective Study

Abstract: The results suggest that immediate loading of freestanding implants stabilized with satellite implants is a successful concept at 3 years observation time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Twenty-five studies, which comprised of prospective studies and RCTs, reported on 2-IODs (Gotfredsen & Holm 2000;Roynesdal et al 2001;Klemetti et al 2003;Cune et al 2004;Ormianer et al 2006;Marzola et al 2007;Cooper et al 2008;Hobkirk et al 2008;Cehreli et al 2010;Kleis et al 2010;Liao et al 2010;Ma et al 2010;Akoglu et al 2011;Cakarer et al 2011;De Kok et al 2011;Engelke et al 2011;Krennmair et al 2011;Al-Nawas et al 2012;B€ uttel et al 2012;El-Sheikh et al 2012b;Elsyad et al 2012;Gadallah et al 2012;Grandi et al 2012;Turkyilmaz et al 2012;Cristache et al 2014). A total of 1572 implants were placed in 786 patients and of these only 35 implants were reported as failures, thus demonstrating a cumulative survival rate between 90.4% and 100% (Table 4).…”
Section: Mandibular 2-iodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-five studies, which comprised of prospective studies and RCTs, reported on 2-IODs (Gotfredsen & Holm 2000;Roynesdal et al 2001;Klemetti et al 2003;Cune et al 2004;Ormianer et al 2006;Marzola et al 2007;Cooper et al 2008;Hobkirk et al 2008;Cehreli et al 2010;Kleis et al 2010;Liao et al 2010;Ma et al 2010;Akoglu et al 2011;Cakarer et al 2011;De Kok et al 2011;Engelke et al 2011;Krennmair et al 2011;Al-Nawas et al 2012;B€ uttel et al 2012;El-Sheikh et al 2012b;Elsyad et al 2012;Gadallah et al 2012;Grandi et al 2012;Turkyilmaz et al 2012;Cristache et al 2014). A total of 1572 implants were placed in 786 patients and of these only 35 implants were reported as failures, thus demonstrating a cumulative survival rate between 90.4% and 100% (Table 4).…”
Section: Mandibular 2-iodsmentioning
confidence: 99%
“…Seven studies employed an immediate loading protocol with reported survival rates ranging between 94% and 100% (patients = 137; implants placed = 274; implants failed = 7). Four of these seven studies reported 100% survival rates over an observation period of 12-36 months (Marzola et al 2007;Engelke et al 2011;B€ uttel et al 2012;Grandi et al 2012).…”
Section: Mandibular 2-iodsmentioning
confidence: 99%